Lithium ion battery and preparation method and application thereof

By using porous ceramic particles as separator materials in lithium-ion batteries, the problem of high consumption of electrolyte by silicon-based negative electrode materials is solved, the liquid retention capacity of the battery and the safety performance of the heat box are improved, and the mechanical and cycling performance of the battery is ensured.

CN119253077APending Publication Date: 2025-01-03ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411220918.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Due to the high consumption of electrolyte by silicon-based negative electrode materials, lithium-ion batteries with high energy density and high capacity, the electrolyte is insufficient in liquid retention, making it difficult to take into account capacity, circulation performance and safety performance.

Method used

Porous ceramic particles are used as separator material, and the proportion of their porosity and silicon mass percentage (P/S ≥ 4) is controlled to increase the liquid retention volume of the electrolyte, and the battery is improved through the thermal conductivity and structural stability of the porous ceramic particles. The heat box safety performance.

Benefits of technology

It realizes that lithium-ion batteries maintain excellent mechanical properties, safety performance and circulation performance based on high energy density and large capacity, avoiding battery softening and heat box safety issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005023002280000071
    Figure BDA0005023002280000071
  • Figure BDA0005023002280000081
    Figure BDA0005023002280000081
  • Figure BDA0005023002280000082
    Figure BDA0005023002280000082
Patent Text Reader

Abstract

The invention discloses a lithium ion battery and a preparation method and application thereof, and belongs to the technical field of new energy. The lithium ion battery provided by the invention comprises a battery cell, the battery cell comprises a positive electrode, a negative electrode and a diaphragm arranged between the positive electrode and the negative electrode; the diaphragm comprises a base material layer and a ceramic coating which are arranged in an overlapped manner, the ceramic coating contains porous ceramic particles; the porosity of the porous ceramic particles is P%, and P is more than or equal to 30 and less than or equal to 70; the negative electrode comprises a negative electrode current collector and a negative electrode coating covering the surface of the negative electrode current collector; the negative electrode coating contains a negative electrode active material; the negative electrode active material contains S% by mass of silicon, and P / S is greater than or equal to 4. The lithium ion battery provided by the invention has excellent safety performance and cycle performance. The invention also provides a preparation method and application of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a lithium ion battery and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in mobile devices due to their fast charging and portability. Currently, more and more people are pursuing high-energy density and high-capacity batteries. For example, 6000mA batteries have become the mainstream of the next generation flagship models of major manufacturers.

[0003] Compared with pure graphite negative electrodes, the energy density of batteries using silicon-containing negative electrodes is higher, reaching 900Wh / L. At present, facing such high-energy and high-capacity batteries, many problems will inevitably arise. For example, the increase in silicon content increases the electrolyte consumption of the battery cell, which requires increasing the electrolyte retention volume of the battery cell. The increase in the retention volume will increase the swelling of the battery cell, resulting in excessive thickness of the battery cell and decreased mechanical properties. Therefore, the increase in battery capacity will lead to a decrease in the safety performance of the battery cell hot box.

[0004] Therefore, it is necessary to design a lithium-ion battery containing a silicon-based negative electrode material, and to ensure its mechanical properties and safety performance on the basis of increasing its liquid retention capacity. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium-ion battery that can ensure the mechanical properties, safety properties and electrochemical properties of the obtained lithium-ion battery on the basis of using silicon-based negative electrode materials and increasing the liquid retention capacity.

[0006] The present invention also provides a method for preparing the lithium ion battery.

[0007] The present invention also provides application of the lithium ion battery.

[0008] According to an embodiment of the first aspect of the present invention, there is provided a lithium ion battery, the lithium ion battery comprising a battery cell;

[0009] The battery cell comprises a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode;

[0010] The diaphragm comprises a substrate layer and a ceramic coating layer which are stacked;

[0011] The ceramic coating contains porous ceramic particles;

[0012] The porosity of the porous ceramic particles is P%, and 30≤P≤70;

[0013] The negative electrode comprises a negative electrode current collector and a negative electrode coating covering the surface of the negative electrode current collector; the negative electrode coating contains a negative electrode active material;

[0014] The negative electrode active material contains S% by mass of silicon, and P / S≥4.

[0015] The lithium-ion battery according to the embodiment of the present invention has at least the following beneficial effects:

[0016] Lithium-ion batteries containing silicon-based negative electrode materials, high energy density and large capacity usually lead to hot box safety issues; at the same time, since silicon-based negative electrode materials consume more electrolyte than traditional graphite negative electrode materials, the increase in silicon content in lithium-ion batteries will lead to insufficient electrolyte retention. The present invention specifically adapts a diaphragm containing porous ceramic particles to the negative electrode containing silicon-based negative electrode materials, solving the problem that lithium-ion batteries are difficult to balance capacity, cycle performance and safety performance. Specifically:

[0017] The liquid retention capacity of silicon-based negative electrode materials themselves is very low, but there are many side reactions in the cycle process, which leads to the consumption of more electrolyte; the amount of electrolyte required for a unit mass of silicon (Si in any form in silicon-based negative electrode materials) is relatively fixed; the pore structure in the porous ceramic particles can accommodate free electrolyte. If the amount of electrolyte fixed by the porous ceramic particles is too small, it cannot support the long cycle of the lithium-ion battery. The lithium-ion battery provided by the present invention defines the ratio between the porosity of the porous ceramic particles and the mass percentage of silicon as P / S≥4; thereby ensuring that the obtained lithium-ion battery has excellent mechanical properties and safety performance, and provides better cycle performance.

[0018] Furthermore, the present invention applies a porous ceramic particle to the diaphragm of the lithium-ion battery, and improves the liquid retention of the battery cell by controlling the porosity and proportion of the porous ceramic particles. Because the electrolyte can be stored in the pores of the porous ceramic particles, the liquid retention volume of the lithium-ion battery can be increased, thereby improving the liquid retention. Because the porous ceramic particles have a good thermal conductivity, they can transfer heat well to help the diaphragm close the pores when thermal runaway occurs. At the same time, due to their own structural stability (need to be within the corresponding porosity range), they can better isolate the contact between the positive and negative electrodes, so that the lithium-ion battery has better hot box safety performance.

[0019] Furthermore, in the lithium-ion battery provided by the present invention, the porous ceramic particles used on the diaphragm also have a skeleton function, that is, on the basis of improving the liquid retention capacity, it will not cause the electrolyte to flow everywhere inside the lithium-ion battery, and the lithium-ion battery will not soften or other mechanical performance degradation.

[0020] According to some embodiments of the present invention, the positive electrode includes a positive electrode current collector and a positive electrode coating covering the surface of the positive electrode current collector; the positive electrode coating contains a positive electrode active material.

[0021] According to some embodiments of the present invention, the positive electrode active material includes at least one of a polyanion material, a layered material, and a spinel material.

[0022] The polyanion material includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.

[0023] The general formula of the layered material is LiMO2, wherein M includes at least one of nickel, cobalt, and manganese. For example, the layered material may be at least one of lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel cobaltate, lithium cobalt manganate, lithium nickel manganate, and lithium nickel cobalt manganate. When the layered material contains ≥2 transition metal ions, the ratio between the transition metal ions is adjusted according to actual needs and materials available on the market, and is not strictly limited here.

[0024] In the layered material, M also includes a doping element; the doping element includes at least one of aluminum, zirconium, magnesium, titanium, boron, and fluorine.

[0025] The spinel material includes lithium manganate (spinel phase).

[0026] According to some embodiments of the present invention, the positive electrode coating further comprises a positive electrode conductor and a positive electrode binder.

[0027] The positive electrode conductive agent includes at least one of carbon nanotubes (CNT) and carbon black (SP).

[0028] The mass ratio of the positive electrode conductive agent to the positive electrode active material is 1:97 to 99; for example, it can be about 1:98;

[0029] The positive electrode binder includes PVDF (polyvinylidene fluoride).

[0030] The mass ratio of the positive electrode conductive agent to the positive electrode binder is 1:0.8 to 1.2; for example, it may be about 1:1.

[0031] According to some embodiments of the present invention, the positive electrode current collector includes aluminum foil.

[0032] According to some embodiments of the present invention, in the S%, S has a value range of 1 to 50. For example, it may be about 3, 5, 6, 7, 8, 9, 10, 12, 15, 18, 20, 30 or about 40.

[0033] According to some embodiments of the present invention, the negative electrode active material includes a silicon-based material.

[0034] According to some embodiments of the present invention, the silicon-based material includes at least one of a silicon-oxygen material and a silicon-carbon material.

[0035] According to some embodiments of the present invention, the negative electrode active material further includes a carbon-based material.

[0036] According to some embodiments of the present invention, the carbon-based material includes at least one of graphite and hard carbon.

[0037] According to some embodiments of the present invention, in the negative electrode, the surface density of the negative electrode active material is 4.6 to 6.2 g / cm 3 .

[0038] According to some embodiments of the present invention, the surface density of the negative electrode active material is 4.8 to 6 g / cm 3 ; For example, it can be about 5g / cm 3 or about 5.5g / cm 3 The surface density in the present invention refers to single-surface surface density.

[0039] According to some embodiments of the present invention, the negative electrode coating further contains a negative electrode binder and a thickener.

[0040] The negative electrode binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (PAA-Li) and polyimide (PI);

[0041] The thickener comprises at least one of sodium carboxymethyl cellulose (CMC) and lithium carboxymethyl cellulose (CMC-Li);

[0042] The mass ratio of the negative electrode active material to the negative electrode binder is 85 to 95:1; for example, it can be about 88:1, 90:1 or about 92:1;

[0043] The mass ratio of the negative electrode active material to the thickener is 85 to 95:1; for example, it may be about 88:1, 90:1 or about 92:1.

[0044] According to some embodiments of the present invention, the negative electrode current collector is selected from copper foil.

[0045] According to some embodiments of the present invention, the material of the substrate layer is at least one of polyethylene, polypropylene, polyester, cellulose, polyimide and aramid.

[0046] According to some embodiments of the present invention, the thickness of the substrate layer is 3-10 μm, for example, about 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or about 9 μm.

[0047] According to some embodiments of the present invention, the material of the porous ceramic particles includes at least one of aluminum oxide, zirconium oxide, aluminum nitride, silicon nitride and silicon carbide.

[0048] According to some embodiments of the present invention, the porosity of the porous ceramic particles is 40-60%. For example, it can be about 42%, 45%, 48%, 50%, 52%, 55% or about 58%. In the present invention, the porosity is the ratio of the volume of the pores to the volume of the porous ceramic particles (true volume + pore volume).

[0049] According to some embodiments of the present invention, the average particle size of the porous ceramic particles is 0.3-3 μm, for example, about 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm or about 2.5 μm.

[0050] According to some embodiments of the present invention, the density of the porous ceramic particles is 0.8-2 g / cm 3 For example, it can be about 1.0 g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 or about 1.2g / cm 3 .

[0051] According to some embodiments of the present invention, in the ceramic coating, the mass percentage of the porous ceramic particles is 40-70%, for example, about 45%, 50%, 55%, 60% or about 65%.

[0052] According to some embodiments of the present invention, the thickness of the ceramic coating is 1-3 μm, for example, about 1.5 μm, 2.0 μm or about 2.5 μm.

[0053] According to some embodiments of the present invention, the ceramic coating further includes a polymer binder.

[0054] According to some embodiments of the present invention, the polymer binder includes at least one of polyvinylidene fluoride, polymethyl methacrylate, polyimide, polysulfone, polyketone, polyetherketone and polytetrafluoroethylene.

[0055] According to some embodiments of the present invention, the value of P / S may specifically be approximately 4.5, 5, 6, 6.5, 7, 8, 9, 9.5, 10, 11, 12, 13, 14 or approximately 15.

[0056] According to some embodiments of the present invention, the lithium-ion battery further includes an electrolyte, and the electrolyte infiltrates the battery core.

[0057] According to some embodiments of the present invention, the electrolyte comprises a lithium salt and an organic solvent.

[0058] The mass percentage of lithium salt in the electrolyte is 5-10%, for example, about 8%.

[0059] The lithium salt includes lithium hexafluorophosphate.

[0060] The organic solvent includes ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC). In the organic solvent, the mass percentage of EC is 20% to 30%, for example, it can be about 25%; the mass percentage of DEC is 20% to 30%, for example, it can be about 25%; the mass percentage of PC is 10% to 20%, for example, it can be about 15%; the mass percentage of PP is 30% to 35%, for example, it can be about 32%; the mass percentage of VC is 1% to 5%, for example, it can be about 3%. In actual production, the composition and proportion of the organic solvent can be adjusted according to actual needs, etc., and are not strictly limited in the present invention.

[0061] According to some embodiments of the present invention, the lithium-ion battery further comprises a battery case, wherein the battery case accommodates the battery cell and the electrolyte.

[0062] According to some embodiments of the present invention, the lithium-ion battery includes at least one of a button battery, a soft-pack battery, a square-shell battery, and a cylindrical battery.

[0063] According to some embodiments of the present invention, when the positive electrode active material of the lithium ion battery is lithium cobalt oxide, the hot box temperature of the lithium ion battery is ≥130° C. For example, it may be about 131° C., 132° C., 133° C. or about 135° C.

[0064] According to some embodiments of the present invention, when the positive electrode active material of the lithium-ion battery is lithium cobalt oxide and the charge and discharge rate is 3.5C, the capacity retention rate of the lithium-ion battery for 800 weeks is ≥ 80%. For example, it can be about 81%, 82%, 83%, 84% or about 85%.

[0065] According to an embodiment of the second aspect of the present invention, a method for preparing the lithium ion battery is provided, the method comprising:

[0066] Providing a diaphragm slurry including the porous ceramic particles, and coating the diaphragm slurry on the surface of the substrate layer to obtain the diaphragm;

[0067] Providing a negative electrode slurry including silicon, and coating the negative electrode slurry on the surface of the negative electrode current collector to obtain the negative electrode;

[0068] The positive electrode, the negative electrode and the separator are assembled to obtain the battery cell.

[0069] Since the preparation method adopts all the technical solutions of the lithium-ion battery of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0070] According to some embodiments of the present invention, the method for preparing the negative electrode slurry comprises mixing the negative electrode active material, a negative electrode binder, a thickener and a negative electrode solvent, wherein the negative electrode solvent comprises water.

[0071] According to some embodiments of the present invention, the preparation of the negative electrode further includes drying, rolling and striping performed in sequence after the coating.

[0072] According to some embodiments of the present invention, the preparation method further comprises providing a positive electrode slurry, and coating the positive electrode slurry on the surface of a positive electrode current collector to obtain the positive electrode.

[0073] According to some embodiments of the present invention, the raw materials for preparing the positive electrode slurry include a mixture of a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and a positive electrode solvent, wherein the positive electrode solvent includes NMP (N-methylpyrrolidone).

[0074] According to some embodiments of the present invention, the preparation of the positive electrode further includes sequentially drying, rolling and striping after the coating.

[0075] According to some embodiments of the present invention, the method for preparing the lithium-ion battery further includes placing the battery cell in the battery shell, injecting the electrolyte, and packaging.

[0076] According to an embodiment of the third aspect of the present invention, there is provided an application of the lithium-ion battery in the field of power batteries, the field of energy storage batteries and the field of 3C small household appliances.

[0077] Since the application adopts all the technical solutions of the lithium-ion battery of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0078] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0079] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0080] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0081] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0082] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0083] Example 1

[0084] In this example, a lithium-ion battery was prepared. The specific process is as follows:

[0085] Preparation of positive electrode:

[0086] The positive electrode active material lithium cobalt oxide (purchased from Xiamen Xiatung New Energy Materials Co., Ltd., D10: 5.4±0.7μm, D50: 15.5±1.2μm, D90: 29.0±2.5μm, BET: 0.16±0.03m 2 g -1 ), mixed positive electrode conductive agent (CNT) and positive electrode binder polyvinylidene fluoride (PVDF) in a mass ratio of 98:1.0:1.0 in an N-methylpyrrolidone solvent system, and then coated on Al foil (positive electrode current collector), and the positive electrode was obtained after drying, rolling and slitting.

[0087] Preparation of negative electrode:

[0088] The negative electrode active material, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system in a mass ratio of 97.8:1.1:1.1, and then coated on a Cu foil. After drying, rolling, and slitting, a negative electrode is obtained, wherein the surface density of the negative electrode active material is 5.8 g / cc; the negative electrode active material is a mixture of graphite and silicon carbon, wherein the silicon content is 5wt% (the subsequent embodiments adjust the silicon content by adjusting the ratio of graphite to silicon carbon); the graphite is Zichen 5C fast-charging graphite; and the silicon carbon is Zhide porous silicon carbon.

[0089] Preparation of diaphragm:

[0090] The porous ceramic particles and PVDF are mixed in a mass ratio of 1:1 to prepare a slurry, and the obtained diaphragm slurry is coated on the surface of the polyethylene substrate layer to form a ceramic coating. The diaphragm is obtained after cutting. The porous ceramic particles used in this example are made of alumina, with an average particle size of 1 μm, a porosity of 30%, and a density of 1.2 g / cm 3 ; The thickness of the substrate layer is 5μm and the thickness of the ceramic coating is 2μm.

[0091] Preparation of electrolyte:

[0092] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 25:25:15:31:4, mass ratio) in a mass ratio of 8:92 is used as the electrolyte of the lithium ion battery.

[0093] Assembly:

[0094] The positive electrode, negative electrode and separator are assembled into a battery cell, where the separator is located between the positive electrode and the negative electrode to prevent short circuit; the battery cell is assembled using the winding method.

[0095] The battery core is placed in an aluminum-plastic film, an electrolyte is injected, and the battery is packaged to obtain a lithium-ion battery. The lithium-ion battery obtained in this example has a designed capacity of 5 Ah and an N / P ratio of 1.04.

[0096] Examples 2 to 16 and Comparative Examples 1 to 5 respectively prepare a lithium ion battery, which is different from Example 1 in that some parameters are different. The specific parameter differences are listed in Table 1.

[0097] Table 1 List of some parameters of the embodiments and comparative examples

[0098]

[0099]

[0100] Test Case

[0101] This example tests the cycle performance and hot box safety performance of the lithium ion batteries obtained in the examples and comparative examples.

[0102] The cycle test adopts the mechanism of 3.5C CC to 4.25V, 4.25V CV to 2.8C, 2.8C CC to4.35V, 4.35V CV to 1.8C, 1.8C CC to 4.5V, 4.5V CV to 0.02C, the charging process ends, and then 0.7CDC to 3.0V, the discharge process ends, and the capacity retention rate at 800 cycles is calculated. The capacity retention rate of this cycle process is called the capacity retention rate at 3.5C rate.

[0103] The method of hot box test is: heat up to the test temperature at a heating rate of 1℃ / min and maintain for 30 minutes. If there is no fire or explosion, it means that the hot box test at this temperature has been passed.

[0104] The results of the above tests are shown in Table 2.

[0105] Table 2 Performance results of lithium ion batteries obtained in Examples and Comparative Examples

[0106]

[0107]

[0108] By comparing Examples 1 to 3 and Examples 15 to 16, it can be seen that, while keeping the silicon content fixed, the porosity of the porous ceramic particles used in the diaphragm is increased, and the hot box safety performance of the obtained lithium ion battery shows a trend of first increasing and then stabilizing. This shows that the setting of the porous ceramic particles has the effect of improving the safety of the hot box, and its mechanism lies in the thermal conductivity and structural stability of the porous ceramic particles; at the same time, the results of Examples 1 to 3 also show that with the increase of the porosity of the porous ceramic particles, the cycle performance of the obtained lithium ion battery shows a trend of increasing and then decreasing. This is because a higher porosity can accommodate more electrolyte, and an important reason for the cycle attenuation is the consumption of electrolyte side reactions; therefore, on the basis of maintaining mechanical properties, more electrolyte brings better cycle performance; but too much electrolyte will also increase the total amount of side reactions to a certain extent, thereby leading to the thickening of the SEI film, and ultimately reducing the electrochemical performance such as cycle.

[0109] By comparing Example 2 and Example 4, and Example 3 and Examples 5 to 6, it can be seen that while maintaining the same porosity of the porous ceramic particles, increasing the silicon content in the negative electrode will reduce the hot box safety to a certain extent and will also reduce the cycle performance to a certain extent.

[0110] By comparing Examples 2 and 7 to 9, it can be seen that if other conditions remain unchanged and the mass percentage of the porous ceramic particles in the ceramic coating is increased, the cycle performance of the resulting lithium-ion battery is improved, but since the electrolyte content is already saturated, its hot box performance remains stable.

[0111] By comparing Examples 10 to 12, 14, and Examples 2, 7 to 9, it can be seen that if the material of the porous ceramic particles is adjusted, the performance difference of the obtained lithium-ion battery is small. This is because the porous ceramic particles used in the embodiments of the present invention are inert and have small differences in thermal conductivity. Therefore, on the basis of limiting their pore structure, they have little effect on the overall performance of the lithium-ion battery.

[0112] By comparing Examples 13 to 14, it can be seen that, within the range given in the present invention, increasing the particle size of the porous ceramic particles can significantly increase the liquid retention capacity, thereby improving the cycle performance and hot box performance.

[0113] By comparing Examples 1 to 14, it can be seen that, on the whole, the hot box safety and cycle performance of the obtained lithium ion battery have a certain improvement trend with the increase of the P / S value, but the improvement trend gradually slows down. However, considering the energy density and production cost of the lithium ion battery, the P / S value selected in actual production can be selected in the range of 4.5 to 15.

[0114] By comparing Example 2 with Comparative Example 1, it can be seen that if the silicon content and the P / S value are not within the range required by the present invention, the cycle performance will be significantly reduced.

[0115] By comparing Example 2 and Comparative Example 2, it can be seen that if the porous ceramic particles are replaced with an equal amount of solid ceramic particles, the cycle performance and the hot box safety performance are simultaneously reduced. This is because compared with solid ceramic particles, the porous ceramic particles not only have better liquid storage capacity, but also have a more stable structure.

[0116] By comparing Example 2 and Comparative Example 3, it can be seen that if the porosity of the porous ceramic particles is not within the range of the present invention, a result similar to that of Comparative Example 1 will occur, that is, the amount of electrolyte is insufficient to support a long cycle.

[0117] By comparing Example 2 and Comparative Example 4, it can be seen that even if the porosity of the porous ceramic particles and the silicon content of the negative electrode are within the range provided by the present invention, if the P / S value is not within the range required by the present invention, it will also lead to a significant decrease in the cycle performance, etc.

[0118] It should be noted that in the industry, in a hot box test at a temperature exceeding 130°C, it is very difficult to pass the test with a temperature increase of 1°C. Compared with the comparative example, the maximum increase in the embodiment of the present invention can reach 5°C, which means that the thermal safety performance of lithium-ion batteries is significantly improved in industrial production.

[0119] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a battery cell; The battery cell comprises a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; The diaphragm comprises a substrate layer and a ceramic coating layer which are stacked; The ceramic coating contains porous ceramic particles; The porosity of the porous ceramic particles is P%, and 30≤P≤70; The negative electrode comprises a negative electrode current collector and a negative electrode coating covering the surface of the negative electrode current collector; the negative electrode coating contains a negative electrode active material; The negative electrode active material contains S% by mass of silicon, and P / S≥4.

2. The lithium-ion battery according to claim 1, characterized in that The material of the porous ceramic particles includes at least one of aluminum oxide, zirconium oxide, aluminum nitride, silicon nitride and silicon carbide.

3. The lithium-ion battery according to claim 1, characterized in that The average particle size of the porous ceramic particles is 0.3-3 μm; and / or the density of the porous ceramic particles is 0.8-2 g / cm 3 .

4. The lithium-ion battery according to claim 1, characterized in that: The thickness of the ceramic coating is 1-3 μm; and / or, in the ceramic coating, the mass percentage of the porous ceramic particles is 40-70%.

5. The lithium-ion battery according to claim 1, characterized in that: The ceramic coating also includes a polymer binder; preferably, the polymer binder includes at least one of polyvinylidene fluoride, polymethyl methacrylate, polyimide, polysulfone, polyketone, polyether ketone and polytetrafluoroethylene.

6. The lithium-ion battery according to claim 1, characterized in that In the S%, the value range of S is 1-50.

7. The lithium-ion battery according to claim 1, characterized in that: In the negative electrode, the surface density of the negative electrode active material is 4.6-6.2 g / cm 3 .

8. The lithium ion battery according to any one of claims 1 to 7, characterized in that: The positive electrode includes a positive electrode current collector and a positive electrode coating covering the surface of the positive electrode current collector; the positive electrode coating contains positive electrode active materials; and / or the lithium ion battery also includes an electrolyte, and the electrolyte infiltrates the battery core.

9. A method for preparing a lithium ion battery according to any one of claims 1 to 8, characterized in that: The preparation method comprises: Providing a diaphragm slurry including the porous ceramic particles, and coating the diaphragm slurry on the surface of the substrate layer to obtain the diaphragm; Providing a negative electrode slurry including silicon, and coating the negative electrode slurry on the surface of the negative electrode current collector to obtain the negative electrode; The positive electrode, the negative electrode and the separator are assembled to obtain the battery cell.

10. Application of the lithium-ion battery according to any one of claims 1 to 8 in the fields of power batteries, energy storage batteries and 3C small household appliances.

Citation Information

Patent Citations

  • Organic / inorganic composite electrolyte and electrochemical device prepared thereby

    CN101385164A

  • Battery diaphragm, preparation method thereof and battery

    CN115275514A

  • Battery monomer, battery and electric device

    CN117039190A

  • Electrode assembly and electrochemical cell comprising the same

    KR1020120098552A

Cited By

  • Battery cell, preparation method therefor, battery device, and electrical device

    WO2026200173A1